TRAP1 controls cell cycle G2–M transition through the regulation of CDK1 and MAD2 expression/ubiquitination. Issue 1 (9th August 2017) - Sisinni, Lorenza; Maddalena, Francesca; Condelli, Valentina; Pannone, Giuseppe; Simeon, Vittorio; Li Bergolis, Valeria; Lopes, Elvira; Piscazzi, Annamaria; Matassa, Danilo Swann; Mazzoccoli, Carmela; Nozza, Filomena; Lettini, Giacomo; et al.
Abstract: Regulation of tumour cell proliferation by molecular chaperones is still a complex issue. Here, the role of the HSP90 molecular chaperone TRAP1 in cell cycle regulation was investigated in a wide range of human breast, colorectal, and lung carcinoma cell lines, and tumour specimens. TRAP1 modulates the expression and/or the ubiquitination of key cell cycle regulators through a dual mechanism: (i) transcriptional regulation of CDK1, CYCLIN B1, and MAD2, as suggested by gene expression profiling of TRAP1‐silenced breast carcinoma cells; and (ii) post‐transcriptional quality control of CDK1 and MAD2, being the ubiquitination of these two proteins enhanced upon TRAP1 down‐regulation. Mechanistically, TRAP1 quality control on CDK1 is crucial for its regulation of mitotic entry, since TRAP1 interacts with CDK1 and prevents CDK1 ubiquitination in cooperation with the proteasome regulatory particle TBP7, this representing the limiting factor in TRAP1 regulation of the G2–M transition. Indeed, TRAP1 silencing results in enhanced CDK1 ubiquitination, lack of nuclear translocation of CDK1/cyclin B1 complex, and increased MAD2 degradation, whereas CDK1 forced up‐regulation partially rescues low cyclin B1 and MAD2 levels and G2–M transit in a TRAP1‐poor background. Consistently, the CDK1 inhibitor RO‐3306 is less active in a TRAP1‐high background. Finally, a significant correlation was observed between TRAP1 and Ki67, CDK1 and/or MAD2 expression in breast, colorectal, and lung human tumour specimens. This study represents the first evidence that TRAP1 is relevant in the control of the complex machinery that governs cell cycle progression and mitotic entry and provides a strong rationale to regard TRAP1 as a biomarker to select tumours with deregulated cell cycle progression and thus likely poorly responsive to novel cell cycle inhibitors. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.